Simulating long-term carbon and nitrogen dynamics of South African maize (Zea mays l.) and sugarcane (Saccharum officinarum l.) cropping systems with APSIM - Van der Laan, Michael (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.